2023
DOI: 10.3390/su15054197
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Ring-Opening Reactions of Epoxidized Linseed Oil in Heterogeneous Catalysis

Abstract: In this study, renewable products with potentially interesting properties and applications were synthesized by functionalizing linseed oil via epoxidation and epoxy ring-opening with carboxylic acids and anhydrides. LDHs (Layered Double Hydroxides), a well-known class of materials used for a wide range of reactions, are the catalysts used in this study, with the overall advantages of facile separation and reusability. In our study, different types of carboxylic acids and anhydrides were employed as reactants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Ring-opening of epoxy rings is further done to add carboxylic and anhydride functionality. 65 The use of peracids and in situ conditions are favored for the epoxidation of linseed oil; a study done by Turco et al used phosphoric acid as a catalyst, used a two-phase model for epoxidation, epoxidation in the oil phase and ring opening in the aqueous phase was carried out. The study concluded that the reactivity of epoxy rings is four times that of soybean oil, and lower temperatures for the reaction are preferred.…”
Section: Epoxidation Of Linseed Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Ring-opening of epoxy rings is further done to add carboxylic and anhydride functionality. 65 The use of peracids and in situ conditions are favored for the epoxidation of linseed oil; a study done by Turco et al used phosphoric acid as a catalyst, used a two-phase model for epoxidation, epoxidation in the oil phase and ring opening in the aqueous phase was carried out. The study concluded that the reactivity of epoxy rings is four times that of soybean oil, and lower temperatures for the reaction are preferred.…”
Section: Epoxidation Of Linseed Oilmentioning
confidence: 99%
“…Epoxidized linseed oil can be functionalized with acids or anhydrides; in a study by Banu et al, linseed oil is epoxidized in the presence of a reusable heterogeneous catalyst, where peracid of acetic acid and hydrogen peroxide is used. Ring‐opening of epoxy rings is further done to add carboxylic and anhydride functionality 65 . The use of peracids and in situ conditions are favored for the epoxidation of linseed oil; a study done by Turco et al used phosphoric acid as a catalyst, used a two‐phase model for epoxidation, epoxidation in the oil phase and ring opening in the aqueous phase was carried out.…”
Section: Epoxidation Of Bio‐based Raw Materialsmentioning
confidence: 99%
“…Although most of the currently available research provides information on CO 2 reduction to methane/methanol and the synthesis of amides, dioxolanes, and dialkyl carbonates, carboxylation reactions with CO 2 as a reactant for incorporation of the entire CO 2 moiety into the new C-C bond formation still require further research [3]. One such class of compounds are carboxylic acids (R-COOH), which are very versatile and important chemicals in the medicinal, pharmaceutical, chemical, and other industries and can also be used as model compounds in the synthesis of other value-added products [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, Kolbe-Schmitt-type reactions are still highly important industrial processes for the production of hydroxybenzoic acids, which are valuable feedstocks for the production of various pharmaceuticals and fine chemicals, while utilizing CO 2 as a cheap, non-dangerous, but environmentally harmful C1 source. Carboxylation of aromatic compounds is exclusively carried out under homogeneous conditions, where the basic catalyst and aromatic substrate are both present in solid form and heated while the CO 2 gas is applied under pressure [5][6][7]. Articles as old as 70 years have been published on such reactions, whereas recent studies still have not managed to significantly improve or thoroughly explain the prevailing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported sustainable functionalization of vegetable oils with organic acids (including cinnamic acid) via epoxy ring-opening reactions using recoverable heterogeneous catalysts (layered double hydroxides-LDH) and environmentally friendly bio-solvents [21]. This concept is further extended and reported in this paper for the tunable synthesis of p-methoxycinnamic acid (p-MCA)-vegetable oil (SBO) bioconjugates to obtain new compounds with UV photoprotective effects having different p-MCA functionalization degrees controlled by the initial epoxidation of the starting material.…”
Section: Introductionmentioning
confidence: 99%